High Levels of Multi Drug Resistant Escherichia coli Pathovars in Preharvest Environmental Samples: A Ticking Time Bomb for Fresh Produce Related Disease Outbreak - Iwu, Chidozie Declan; Kayode, Adeoye John; Igere, Bright Esegbuyota; Okoh, Anthony Ifeanyin (Frontiers in Environmental Science, 2022)
The preharvest environment provides a suitable platform for the emergence and dissemination of multidrug resistant pathogenic bacteria. This could be detrimental to public health and may lead to fresh produce related disease outbreaks when transferred to the food web. This study evaluated the occurrence and antibiogram fingerprints of the pathogenic strains of Escherichia coli (E. coli) recovered from irrigation water and agricultural soil samples in fresh produce farms in the Eastern Cape Province, South Africa. E. coli was isolated, pathotyped and screened for antibiogram fingerprints using standard cultural and molecular methods. An antibiogram-based K-means cluster analysis and neighbour-joining dendrogram was used to elucidate the relatedness of the isolates. Of the confirmed isolates, 37% harboured at least one of the screened virulence genes (VGs) that encode for intestinal and extraintestinal E. coli pathovars. The most prevalent pathovar/associated VG in all the samples was Enterohemorrhagic E. coli/stx2. Of all the antimicrobials tested, E. coli pathovars conferred the highest resistance against ampicillin with a median single antimicrobial resistance index of 0.23 (IQR: 0.95 to 0.39, 95% CI: 0.16 to 0.27) for pathovars from irrigation water and 0.01 (IQR: 0.01 to 0.03, 95% CI: 0.01 to 0.03) for pathovars from agricultural soil. About 60% and 20% of the pathovars from irrigation water and agricultural soil were multi drug resistant with a median multiple antimicrobial resistance index of 0.41 (IQR: 0.25 to 0.52, 95% CI: 0.31 to 0.47) and 0.38 (IQR: 0.23 to 0.66, 95% CI: 0.19 to 0.69) respectively. The most prevalent resistance genes detected were sulI, catII, tetA and AmpC across all sample types. The blaTEM was the most prevalent extended-spectrum β-lactamase resistance gene detected. A positive correlation between the phenotypic and genotypic AMR profiles of the pathovars in irrigation water samples, r=0.6, p≤0.01 and agricultural soil samples, r=0.8, p≤0.01 was recorded. The antibiogram based dendrogram generated 11 and 7 clades from irrigation water and agricultural soil samples respectively, indicating that the isolates are highly diversified. The findings revealed the occurrence of highly diversified multidrug resistant E. coli pathovars in the preharvest environment, indicating potential public health threats.